On Some Convergence Theorem of Double Laplace Transform (Journal of Informatics and Mathematical Sciences, 2014)
Starting with convergence and absolute convergence of double Laplace integral uniform convergence of double Laplace transform is presented. Finally, a Volterra Integro-Partial Differential Equation is solved by using double Laplace transform.
Keywords: Double Laplace transform; Inverse Laplace transform; Integro-Partial differential equation; Partial derivatives